Analgesic and Anti-Inflammatory Effects of an Extract and Flavonoids from Artemisia Herba-Alba and Their Mechanisms of Action - Qnais, E.; Raad, D.; Bseiso, Y. (Нейрофизиология, 2014)
Artemisia herba-alba (A. h.-a.) has wide use in traditional medicine for the relief of coughing, healing external wounds, and treatment of pain associated with gastrointestinal disturbances. We investigated in vivo antinociceptive and anti-inflammatory activities of an aqueous extract (aq. ex.) and two isolated compounds obtained from aerial parts of A. h.-a. The
analgesic effects of aq. ex. (10, 31.6, 100, 316, and 1000 mg/kg), astragalin, and eupatilin
(both, 0.316, 1, 3.16, 10, 31.6, and 100 mg/kg) were studied using the hot-plate test in mice
and formalin test in rats. The effects were compared with those of 5 mg/kg morphine. Dosedependent analgesic effects of aq. ex., astragalin, and eupatilin were clearly manifested in
both hot-plate assay and early and late phases of formalin-induced paw licking. These effects
were significantly but partly reduced by the opioid receptor antagonist naloxone (5 mg/kg).
The same range of doses of aq. ex., astragalin, and eupatilin caused dose-dependent suppression of carrageenan-induced paw edema in rats. Thus, we demonstrated that A. h.-a. possesses
noticeable antinociceptive and anti-inflammatory activities; our data support the reasons for
using this plant as a remedy for treatment of pain and inflammation. Antinociceptive and
anti-inflammatory actions of A. h.-a. are considerably related to the presence of astragalin
and eupatilin Білий полин (Artemisia herba-alba – A. h.-a.) знаходить широке застосування в традиційній медицині. Його вживають
для припинення кашлю, лікування ран, вгамування болю
при шлунково-кишкових розладах та ін. В експериментах in
vivo ми досліджували антиноцицептивні та протизапальні
ефекти водного екстракту (в. екс.) та двох окремих компонентів, отриманих із надземних частин A. h.-a. Аналгетичні
ефекти в. екс. (10, 31.6, 100, 316 та 1000 мг/кг), астрагаліну та еупатиліну (обидва в дозах 0.316, 1, 3.16, 10, 31.6 та 100
мг/кг) визначались у тесті «гарячої платівки» на мишах та
формаліновому тесті на щурах; ці ефекти порівнювали з такими морфіну. Залежні від дози аналгетичні впливи в. екс.,
астрагаліну та еупатиліну яскраво проявлялись як у тесті
«гарячої платівки», так і в перебігу ранньої та пізньої фаз
реакції лизання кінцівки, індукованої ін’єкцією формаліну.
Ці ефекти усувались, проте лише частково, антагоністом
опіоїдних рецепторів налоксоном (5 мг/кг). Аналогічні дози
в. екс., астрагаліну та еупатиліну забезпечували дозозалежне пригнічення індукованого карагенаном набряку кінцівки
у щурів. Таким чином, ми продемонстрували, що для A. h.-
a. характерні істотні антиноцицептивна та протизапальна
властивості. Наші дані підтверджують обгрунтованість застосування цієї рослини як лікувального засобу в традиційній медицині. Згадані властивості A. h.-a. в істотній мірі залежать від наявності в її складі астрагаліну та еупатиліну.